Investigation of the Composite Motor Load in the Presence of Higher Harmonics in the Electrical Network - Ya. E. Shklyarskiy; K. K. Lobko; Yu. N. Kuznetsova; M. S. Vorobyov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article discusses the methods of substitution of a compound motor load as a consumer of higher harmonics. Two substitution schemes were used. The calculation of the complex resistance against them was compared with the results of simulation modeling. The simulation was carried out in the MATLAB Simulink environment, with the use of the Specialized Power Systems library, in which a simulation model with motors and a source of harmonic distortion was developed. Five asynchronous motors with a squirrel-cage rotor of the AIR brand with powers varying from 0.75 to 5.50 kW were selected for the study. The simulation was carried out at different motor loads. The shaft torque varied with values of 50; 70; 90 and 100 % of the nominal values of each motor. A six-pulse diode rectifier was used as a source of harmonic currents in the network, generating harmonics with numbers 5, 7, ..., 25, corresponding to a pulse rate equal to six. Oscillograms of currents and voltages were recorded at the point of common connection of asynchronous motors and the rectifier, which were subsequently used to calculate the complex resistance. Based on the results of the work, amplitude-frequency and phase-frequency characteristics of the impedance of a composite motor load were obtained, the analysis of which revealed the incongruence of calculation methods with simulation modeling. Conclusions have been drawn on the need to continue research in this direction, since there are qualitative discrepancies in the functional dependence of the complex resistance on the harmonic number with the experimental data obtained for a single asynchronous motor. The results of the work can be used in calculating the voltage distortion factor and modeling modes associated with higher harmonics both at existing enterprises and during their design, which will increase the reliability and efficiency of electrical networks.